Sistema de información para un banco inmobiliario en los procesos de restablecimiento de la población desplazada por el conflicto armado colombiano - Cely Pulido, John William; Daniel, Héctor Ricardo; Rodríguez, Sergio E; Diaz, Juan Pablo; Zora, Javier E. (Ingeniería, 2000)
The System was designed for contributing concrete solutions to the Programs of Lands and Housing directed the Displaced Population PD. The general principle, is the Support for the realization of the Plans of Reestablishment in the rural and urban environment that they carry out the institutions in charge of the PD; the generation of graphics, charts and indexes, leaving of predial information on the analysis areas, will be some of the tools used for the taking of decisions in the outlined objective. For the urgency of knowing that benefits would generate this purpose, you design for an area pilot that is the Department of Cundinamarca.